Pengaruh Gaya Kepemimpinan, Lingkungan Kerja dan Loyalitas Terhadap Kinerja Karyawan pada PT Hardosoloplast di Karanganyar - Hartanto, Lius; Sutarno (Teewan Journal Solutions, 2025)
Human resources are the key to the survival of an organization, because human resources are organizational assets that are relatively difficult for other organizations to imitate. This is due to the nature of human resources which are not fixed and continue to move flexibly following every change that occurs in the environment. This research aims to analyze the significance of the influence of leadership style on employee performance at PT Hardosoloplast in Karanganyar. Analyzing the significance of the influence of the work environment on employee performance at PT Hardosoloplast in Karanganyar. Analyzing the significance of the influence of loyalty on employee performance at PT Hardosoloplast in Karanganyar. This research uses employees of PT Hardosoloplast in Karanganyar as objects. The research method used is a quantitative method, using SPSS 25.0, to analyze the data. The data sources used in this research are primary data and secondary data. The population in this study were employees of PT Hardosoloplast. The sample used in this research was 97 employees of PT Hardosoloplast. The sampling technique uses proportional cluster random sampling technique. The data collection techniques used were questionnaires, observation and literature study. Data analysis techniques use descriptive analysis, multiple linear regression test, t test, F test, and coefficient of determination test.The results of multiple linear regression analysis in this study are Y = 4.569 + 0.738 X1 + 0.039 X2 + 0.038 X3 + e. The t test results show that leadership style has a significant effect on the performance of PT Hardosoloplast expedition employees in Karanganyar. The work environment has no significant effect on the performance of PT Hardosoloplast expedition employees in Karanganyar. Loyalty has no significant effect on the performance of PT Hardosoloplast expedition employees in Karanganyar.